2010
DOI: 10.1177/1359104509352893
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient psychotherapy practice with adolescents following psychiatric hospitalization for suicide ideation or a suicide attempt

Abstract: Outpatient treatment is standard care for adolescents discharged following a psychiatric hospitalization. There is little research, however, on the amount and types of psychotherapy these clients receive in the community. We examined therapy attendance and therapist report of outpatient therapy practice with adolescents discharged from psychiatric hospitalization following either a suicide attempt or severe suicidal ideation in the Northeastern USA. Therapists (n = 84) completed a packet of self-report questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These high lifetime and past month rates of alcohol and marijuana use (see Table 1) are consistent with the rates of substance use reported in other psychiatric samples of adolescents (Deas-Nesmith, Campbell, & Brady, 1998; Martin, Milich, Martin, Hartung, & Haigler, 1997). It is also noteworthy that there were substantial increases in substance use rates over the 18 month follow-up period, despite the fact that the majority of this sample received mental health treatment ( M = 8.1 sessions, SD = 4.7 sessions) following discharge from the hospital (Spirito et al, 2011). …”
Section: Discussionmentioning
confidence: 91%
“…These high lifetime and past month rates of alcohol and marijuana use (see Table 1) are consistent with the rates of substance use reported in other psychiatric samples of adolescents (Deas-Nesmith, Campbell, & Brady, 1998; Martin, Milich, Martin, Hartung, & Haigler, 1997). It is also noteworthy that there were substantial increases in substance use rates over the 18 month follow-up period, despite the fact that the majority of this sample received mental health treatment ( M = 8.1 sessions, SD = 4.7 sessions) following discharge from the hospital (Spirito et al, 2011). …”
Section: Discussionmentioning
confidence: 91%
“…Recruitment for our study occurred between 2006 and 2010. Comparison studies with low rates of involvement in treatment, such as the study by Spirito et al 1992, 21 were published much earlier than that, and a more recent study from that same hospital published in 2011 9 found higher levels of treatment attendance than in the 1992 study. Changes in patterns of treatment utilization for these different cohorts could be due to factors such as changes in insurer willingness to fund an array of services and a greater awareness of the importance of receiving ongoing mental health treatment following a period of intensive care such as hospitalization.…”
Section: Discussionmentioning
confidence: 97%
“…8 The high rates of service use in these samples may be due to the fact that, unlike in the studies reviewed above, the participants were psychiatrically hospitalized, which suggests that they represented higher risk samples. Nonetheless, Spirito et al reported that, during a 3-month period after discharge, 18% terminated outpatient therapy against therapist advice, 9 and James et al found that, over a 30-month follow-up period, 28% of their sample of children and adolescents failed to receive any treatment following their first psychiatric hospitalization, 10 thus offering a less optimistic view of patterns of service use. In a review of data concerning children and adolescents who received inpatient psychiatric care, Daniel et al reported that, in general, two thirds or more of psychiatrically hospitalized youth received treatment of some kind following discharge from the hospital.…”
mentioning
confidence: 99%
“…To more fully test the specificity of SIDI, future research should assess and control for other dimensions of negative affect. Finally, we included two comparison conditions, including a SC condition that captures non-specific treatment effects and mirrors a common form of treatment often provided in the community (Koekkoek et al, 2010; Andrews, 1993; Spirito et al, 2011). However, neither comparison condition was active or included empirically-supported elements.…”
Section: Discussionmentioning
confidence: 99%